(untitled) (Applied Biological Research, 2017)
Seed storage protein profiling and RAPD were used in present study for the analysis of genetic diversity among 15 chickpea genotypes. SDS-PAGE of seed storage protein differentiated 15 genotypes into three major clusters. RAPD analysis was done using highly polymorphic ten primers which amplified 104 bands with 2.70 average polymorphic bands. RAPD analysis reported 24.4 average per cent polymorphism and highest in OPH-03. OPH-19 reported highly informative primer based on PIC and MI value. Similarity coefficients of RAPD data were ranged from 0.55 to 0.95. Dendrogram generated three major clusters which distinguished Fusarium wilt susceptible and resistant genotypes in cluster I and cluster II, respectively, whereas cluster III included both resistant and susceptible genotypes. RAPD marker was found more informative than seed storage protein profiling for diversity analysis. Further, no specific banding was detected that could discriminate resistant from susceptible genotypes critically.